The Development of Gesell’s Theory Activity Plan for Improving Ability to Use Small Muscles of Intellectual Disabilities Children - Naphasawan Ritdech and Sutthiporn Boonsung (International Journal of Advanced Science and Technology, 2020)
The purposes of this research were: 1) To develop Gesell's theoretical activity plan to improve the ability to use small muscles of intellectual disabilities children at Mahachakri Sirindhorn Special Education Center Nakhon Nayok Province, 2. To study the ability to use small muscles of intellectual disabilities children at Mahachakri Sirindhorn Special Education Center Nakhon Nayok Province after use Gesell's theoretical activity plan. Sample used in this research random with purposive sampling were 2 intellectual disabilities Children with are children who come to receive services at the intelligence preparation room of Mahachakri Sirindhorn Special Education Center Nakhon Nayok Province. These 2 children were chosen to develop had small muscles development not strong such as: using fingers, and the coordination between the eyes and hands. Tools used in the study are 1) Gesell's theoretical activity package consisting of 5 plans 2) Muscular ability assessment forms for intellectual disabilities children, and 3) Activity recording form. The study indicated thattThe result of Gesell's theory of activity package development for improving ability to use small muscles of intellectually disabilities children found that the activity package was effective according to standard criteria. The ability to use small muscles of intellectually disabilities children who learned by Gesell's activity package high level